شعرية العتبات السردية عند بدر شاكر السياب - لاعج, معتوق (كلية الأدب العربي والفنون, 2024)
يتعرض موضوع المذكرة إلى الكشف عن أهم الأحداث والمواقف التي مر بها الأديب بدر شاكر السياب وكيف أعطى تدفقا للمعاني واللغة في صنع الصورة الشعرية المعاصرة، فقد تحولت القصيدة الحديثة بفضله إلى نسج حي يموج بالحركة الدرامية ويزخر بتجارب الحياتية الخالصة الإحساس ونقية المشاعر فكانت له الأفضلية في رسم ملامح وعناصر والخطوط العريضة لتركيب الصورة الشعرية الجديدة المبنية على توظيف السرد في الشعر The subject of the memorandumisexposed to the most important event and positions that the writer bader shaker al- sayab and how he gave flow of meaning and language in the making of contemporarypoeti image hesbecome a favorite poems to the malle heapmosqueText o the dramaticmovementintroducedmocking and chronic life experienceinto pure senses and feelings intoformal traits and elements of the modern the new poetic image based on employing narration in poetry.
Keywords: بدر شاكر السياب - تقنيات-الشعرية- العتبات السردية: Bader shaker alsayab - Techniques - Poetics - Narrative thresholds